On an nth-order infinitesimal generator and time-dependent operator differential equation with a strongly almost periodic solution - Aribindi Satyanarayan Rao (International Journal of Mathematics and Mathematical Sciences)
In a Banach space, if u is a Stepanov almost periodic solution of a certain nth-order infinitesimal generator and time-dependent operator differential equation with a Stepanov almost periodic forcing function, then u,u′,…,u (n−2) are all strongly almost periodic and u (n−1) is weakly almost periodic.